Fully Automated Ground Motion Selection Platform Considering Multiple Seismic Source Contributions for Seismic Evaluation of Existing Buildings in Indonesia - Alexander, Nick; Irsyam, Masyhur; Asrurifak, Muhammad; Hendriyawan, Hendriyawan; Faizal, Lutfi (Journal of Engineering and Technological Sciences, 2025)
Buildings throughout Indonesia are at risk of experiencing damaging earthquake events from multiple sources within shallow crustal and subduction zones. Seismic assessments per SNI 9273: 2024 require earthquake acceleration time series, but a public web-based platform that can facilitate this need was not yet available. Thereby, it became urgent to investigate the possibility of developing an automated engineering tool that can determine hazard-consistent ground motion set with good target-match accuracy for regions where multiple seismic source contribution is prevalent. The investigation was conducted through the development of a fully-automated ground motion selection and scaling platform specifically customized to facilitate the seismic evaluation and retrofit of existing buildings throughout Indonesia, limited to upper bound period range of 3 s. This platform has been officially launched for public access by the Indonesian Ministry of Public Works to enhance the efficiency and accuracy of seismic assessments with the broader goal of improving seismic safety. Completion and test case validation of the platform confirmed that such useful tool can be developed provided that the following key features are incorporated: (1) specifically-defined scope of application; (2) comprehensive data integration to consider multiple seismic source contribution; and (3) modified greedy selection algorithm to enhance target-match accuracy